1990
DOI: 10.1111/j.1151-2916.1990.tb09786.x
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Sintering of Ultrafine MgO‐ZrO2 and (MgO, Y2O3)‐ZrO2 Powders

Abstract: Chemical coprecipitation was used to prod~~ce ultrafine and easily sinterrMc MsogcpbiliVa and (Mg0,Y203)stabilized Zr02 porrders. The sintering behavior is very sensitive to post-precipitation washing because Yhard" agglomerates form when the precipitated gels are washed with water, whereas "soft" agglomerates form when they are washed with ethanol. The soft agglomerates pack oniformly, resnlting in hshrinkage of powder compacts to neartheoretical density. The hard agglomerates result in compacts which have re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(62 citation statements)
references
References 10 publications
4
57
1
Order By: Relevance
“…This result differs from Readey et al, who reported that green densities between water-dispersed and ethanol-dispersed ZrO2 powders differed by 3.5% after pressing at 70 MPa, i.e., the ethanol-dispersed ZrOa had a 40% green density and the water-dispersed ZrOa was 36.5% dense [21].…”
Section: Resultscontrasting
confidence: 84%
See 1 more Smart Citation
“…This result differs from Readey et al, who reported that green densities between water-dispersed and ethanol-dispersed ZrO2 powders differed by 3.5% after pressing at 70 MPa, i.e., the ethanol-dispersed ZrOa had a 40% green density and the water-dispersed ZrOa was 36.5% dense [21].…”
Section: Resultscontrasting
confidence: 84%
“…The higher sintered densities achieved in water-dispersed system for short sintering time is due to a higher agglomerate density, and consequently faster kinetics of intraagglomerate densification. In the work of Readey et al [21], the ethanol-dispersed sample with a higher green density showed similar densification behavior to the water-dispersed samples. That means the lower green density of water-dispersed system did not result in retarded densification kinetics at low temperature sintering.…”
Section: Resultsmentioning
confidence: 61%
“…4b, whereas the lower S BET values after FD is a direct effect of the formation of hard agglomerates. For both EW/AD and FD powders, the electron diffraction patterns show tetragonal zirconia 45,46 , along with the interplanar spacing of 0.29 nm for the (101) t plane, once again consistent with the values reported for tetragonal symmetry 47,48 .…”
Section: Powder Characteristics After Dehydrationsupporting
confidence: 85%
“…Nonetheless, these advantages are largely offset by the formation of hard agglomerates, which persists as a serious drawback of coprecipitated YSZ powders [14]. Hard agglomerates are formed by strong intercrystallite bonding during removal of the surface hydroxyl groups at the www drying stage, and are consolidated in the calcination step by the following reaction [15][16][17]:…”
Section: Introductionmentioning
confidence: 99%